Propranolol treatment in children with tetralogy of Fallot alters the response to isoprenaline after surgical repair. Issue 2 (August 1988) - Barazzone, C; Jaccard, C; Berner, M; Dayer, P; Rouge, J C; Oberhansli, I; Friedli, B
Abstract : When propranolol is given to prevent hypoxaemic episodes in children with tetralogy of Fallot who are awaiting operation it is advisable to continue the treatment until shortly before the induction of anaesthesia. Because catecholamines are often required to maintain adequate cardiac output after surgical correction the effect of preoperative treatment with beta blockers on the response to isoprenaline after the operation was investigated in nine children given propranolol before operation and nine who were not. They were studied three and 24 hours after cardiopulmonary bypass. The haemodynamic response to increasing doses of infused isoprenaline was monitored. Immediately after cardiopulmonary bypass the response to isoprenaline was significantly blunted in the patients who had been given propranolol before operation. Their dose-response curve lay to the right of that for patients not given propranolol, and this indicates competitive inhibition. Propranolol concentrations in the blood and myocardium correlated significantly with the heart rate response to isoprenaline. Twenty four hours after operation the isoprenaline response was similar in both groups and concentrations of propranolol in the blood were minimal or undetectable. beta Blockers given up to the time of operation significantly altered the postoperative response to catecholamines.